2012
DOI: 10.2527/jas.2011-4533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of linear, skewed-linear, and proportional hazard models for the analysis of lambing interval in Ripollesa ewes1

Abstract: Lambing interval is a relevant reproductive indicator for sheep populations under continuous mating systems, although there is a shortage of selection programs accounting for this trait in the sheep industry. Both the historical assumption of small genetic background and its unorthodox distribution pattern have limited its implementation as a breeding objective. In this manuscript, statistical performances of 3 alternative parametrizations [i.e., symmetric Gaussian mixed linear (GML) model, skew-Gaussian mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Our estimates about goodness of fit suggested that linear models must be ruled out from AFL data analysis, whereas PWPH models were an appealing alternative with preferable statistical performances. This conclusion agreed with previous studies that advocated the superiority of survival analysis techniques when handling time interval data such as lambing interval in sheep (Casellas et al, 2012), age at first calving (García et al, 2014), or fertility-and longevity-related traits in cattle (Caraviello et al, 2004;Schneider et al, 2005Schneider et al, , 2006MacNeil and Vukasinovic, 2011). Within this context, the implementation of proportional hazards models seems a reasonable alternative for AFL data.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Our estimates about goodness of fit suggested that linear models must be ruled out from AFL data analysis, whereas PWPH models were an appealing alternative with preferable statistical performances. This conclusion agreed with previous studies that advocated the superiority of survival analysis techniques when handling time interval data such as lambing interval in sheep (Casellas et al, 2012), age at first calving (García et al, 2014), or fertility-and longevity-related traits in cattle (Caraviello et al, 2004;Schneider et al, 2005Schneider et al, , 2006MacNeil and Vukasinovic, 2011). Within this context, the implementation of proportional hazards models seems a reasonable alternative for AFL data.…”
Section: Resultssupporting
confidence: 89%
“…Note that both approaches provide similar estimates and departures must be partially attributable to the absence of systematic, permanent and genetic factors when computing the baseline hazard function under model PWPH3; the Kaplan-Meier estimate is computed from raw AFL data and all additional sources of variation are implicitly included. The need for this kind of additional modeling of the standard Weibull baseline function has been previously demonstrated on longevity (Tarrés et al, 2005;Casellas et al, 2008) and fertility data (Casellas and Bach, 2012), although this should not be viewed as a weakness of the survival analysis techniques but a remarkable advantage in terms of flexibility of the PWPH (Casellas, 2007) model. Systematic and genetic influences on AFL Although three systematic effects were included in the analytical model, only the season of birth of the ewe had relevant influences on the AFL under PWPH3 parameterization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations